2010
DOI: 10.1007/s00394-010-0147-2
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin C levels in blood are influenced by polymorphisms in glutathione S-transferases

Abstract: The correspondence of lower vitamin C levels with non-functional GST isoenzymes may indicate a causal connection between two antioxidant defence pathways, also the underlying mechanism is not yet clear. It seems that supplementation by natural antioxidants is particularly important for subjects with unfavourable genetic makeup and in those exposed to oxidative stress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 51 publications
0
23
0
Order By: Relevance
“…The GSTM1-null genotype appeared to be associated with increased plasma levels of ascorbate when the dietary intake of vitamin C also was high (6, 25). Conversely, the populations with low dietary intake of vitamin C and the GSTM1 deletion showed lower plasma ascorbate levels than did individuals with functional GSTM1 at the same intake level (11, 42). This suggests a heretofore uncharacterized interaction between dietary vitamin C, plasma ascorbate, and the activity of GSTs, possibly involving lipid peroxidation products or environmental toxins.…”
Section: Glutathione S-transferasesmentioning
confidence: 87%
See 1 more Smart Citation
“…The GSTM1-null genotype appeared to be associated with increased plasma levels of ascorbate when the dietary intake of vitamin C also was high (6, 25). Conversely, the populations with low dietary intake of vitamin C and the GSTM1 deletion showed lower plasma ascorbate levels than did individuals with functional GSTM1 at the same intake level (11, 42). This suggests a heretofore uncharacterized interaction between dietary vitamin C, plasma ascorbate, and the activity of GSTs, possibly involving lipid peroxidation products or environmental toxins.…”
Section: Glutathione S-transferasesmentioning
confidence: 87%
“…Two studies, one in a Chinese cohort (96) and another with a mixed population in Canada (11), showed no differences in vitamin C status associated with the GSTM1 genotype. In addition, a study of factory workers in Slovakia reported an overall decline in plasma vitamin C levels associated with the GSTM1-null genotype (42). …”
Section: Glutathione S-transferasesmentioning
confidence: 99%
“…Polymorphisms in the SLC23A1 gene and changes in the glutathione S-transferase (GST) gene were also associated with the concentrations of ascorbic acid [26]. GST represents a family of enzymes that catalyze the reaction between glutathione and ROS resulting in the elimination of toxic metabolites.…”
Section: Genetic Determinants Of Vitamin C Statusmentioning
confidence: 99%
“…Specifically the genetic variations influencing the serum concentrations of ascorbic acid are haptoglobin (Hp) polymorphism (Langlois et al, 1997(Langlois et al, , 2000, polymorphisms of transporters for vitamin C (Timpson et al, 2010) and deletion polymorphisms of glutathione-S-transferase (Horska et al, 2011).…”
Section: Introductionmentioning
confidence: 99%